Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1099/ijs.0.009845-0
|View full text |Cite
|
Sign up to set email alerts
|

Meridianimaribacter flavus gen. nov., sp. nov., a member of the family Flavobacteriaceae isolated from marine sediment of the South China Sea

Abstract: A Gram-staining-negative, rod-shaped marine bacterium, designated strain NH57NT, isolated from sandy sediment in the Mischief Reef of the South China Sea, was characterized based on its physiological and biochemical features, fatty acid profile and phylogenetic position. 16S rRNA gene sequence analysis revealed a clear affiliation with the family Flavobacteriaceae. Strain NH57NT showed the closest phylogenetic relationship with members of the genera Gaetbulibacter, Gelidibacter, Subsaxibacter, Subsaximicrobium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Corallibacter vietnamensis gen. nov., sp. nov. Asker et al (2007), Bercovich et al (2008), Bowman & Nichols (2005), Ivanova et al (2004), , Lau et al (2005), Nedashkovskaya et al (2005aNedashkovskaya et al ( , b, 2006aNedashkovskaya et al ( , 2008Nedashkovskaya et al ( , 2009bNedashkovskaya et al ( , 2010, Pinhassi et al (2009), Romanenko et al (2009), Wang et al (2010) and this study.…”
supporting
confidence: 55%
“…Corallibacter vietnamensis gen. nov., sp. nov. Asker et al (2007), Bercovich et al (2008), Bowman & Nichols (2005), Ivanova et al (2004), , Lau et al (2005), Nedashkovskaya et al (2005aNedashkovskaya et al ( , b, 2006aNedashkovskaya et al ( , 2008Nedashkovskaya et al ( , 2009bNedashkovskaya et al ( , 2010, Pinhassi et al (2009), Romanenko et al (2009), Wang et al (2010) and this study.…”
supporting
confidence: 55%
“…Maximum absorption peak of pigments is at 452 nm and the next shoulder peak is at 480 nm. A member of the family Flavobacteriaceae, class (Wang et al, 2010); 6, Subsaxibacter broadyi P7 T (Bowman & Nichols, 2005); 7, Subsaximicrobium (n52; Bowman & Nichols, 2005). n, Number of type strains in each genus; +, positive; 2, negative; W, weakly positive; ND, no data available; V, varies among different species within the same genus.…”
Section: Strain Jc2132mentioning
confidence: 99%
“…Comparative 16S rRNA gene sequence analysis indicated that the novel strain is phylogenetically most closely affiliated to the genera Meridianimaribacter and Mangrovimonas , members of the family Flavobacteriaceae . The genus Meridianimaribacter was proposed by Wang et al (2010) and at the time of writing comprises a single species with validly published name, Meridianimaribacter flavus . The genus Mangrovimonas was recently proposed by Li et al (2013) with the description of a single novel species, Mangrovimonas yunxiaonensis .…”
mentioning
confidence: 97%